Exploitation and use of solar energy to Synthesis and characterization of Pure and Cobalt-doped NiO Nanoparticles by spray pyrolysis - يونس, سعداني; سفيان, سليماني; طارق, قويضي (University Of El Oued, 2020)
"Abstract: this work is concern the study of the structural, optical and electrical characteristics of thin -films of pure nickel oxide (NiO), and cobalt (Co) doped (NiO) using (0, 1 ,3 ,5) % concentrations, where the deposition of thin-films is realized on glass substrates under temperature (400𝐶°) by spray pyrolysis technique, X- ray diffraction results have shown that the thin films prepared have a cubic crystalline structure. The main characteristic peaks are assigned to the (111) and (200) planes. The transmittance of Co doped nickel oxide thin films increases rapidly as the wavelength increases in the range of (300 - 350) nm. The band gap values decreases when the Co concentration increases and these values are between 3.49 eV and 3.65 eV. Urbach’s energy increases with the concentration of Co, and the perfect film doped conductivity is obtained for the percentages 1%. Keywords: Spray Pyrolysis Technique (SPT); NiO Thin Films; Transparent Conductive Oxides (TCO); Cobalt." "ملخص : والنيكل ، (NiO) يهتم هذا العمل بدراسة الخصائص التركيبية والبصرية والكهربائية للأغشية الرقيقة لأكسيد النيكل النقي باستخدام تركيزات ) 0،1،3،5 (٪ ، حيث ترسب طبقة رقيقة. - يتم تحقيق الأغشية على ركائز (Co) المخدر بالكوبالت زجاجية تحت درجة حرارة ) 400 درجة مئوية( بتقنية الانحلال الحراري بالرش ، وقد أظهرت نتائج حيود الأشعة السينية أن الأغشية الرقيقة المحضرة لها بنية بلورية مكعبة. يتم تعيين القمم المميزة الرئيسية للطائرات ) 111 ( و ) 200 (. تزداد 350 ( نانومتر. - نفاذية الأغشية الرقيقة لأكسيد النيكل المشوب بالكربون بسرعة مع زيادة الطول الموجي في نطاق ) 300 وتتراوح هذه القيم بين 3.49 فولت و 3.65 فولت. تزداد طاقة طاقة اورباخ Co تنخفض قيم فجوة النطاق عندما يزيد تركيز .٪ ويتم الحصول على الموصلية المثالية للغشاء المشبع بالنسبة المئوية 1 ، الكلمات المفتاحية : تقنية الانحلال الحراري بالرش Co مع تركيز كوبالت. ؛ )TCO( أكاسيد موصلة شفافة ؛ NiO أفلام رقيقة ؛ )SPT("
Energies renouvelables en mecanique مذكرة ماستر تخصص
Keywords: Keywords: Spray Pyrolysis Technique (SPT); NiO Thin Films; Transparent Conductive Oxides (TCO); Cobalt.; الكلمات المفتاحيه : تقنية الانحلال الحراري بالرش (SPT) . النيكل NiO . الكوبالت CO . الطبقات الرقيقه .اكاسيد موصله شفافه TCO